The Singapore lion a biography of S. Rajaratnam - Ng, Irene 1963- (Institute of Southeast Asian Studies, 2010)
"Irene Ng has written a book that gives a comprehensive portrayal of Mr Rajaratnam - one of Singapore's outstanding leaders who played a crucial part in the momentous and crisis-ridden transition to independence. This is a book about the man and his wisdom. One would fail to appreciate him until one reads this absorbing book and reflects on the acuity and breadth of his insights and his wisdom." - S. R. Nathan, President of Singapore "In the course of a 33-year career in diplomacy, I met many great leaders. Having done so, I can confidently assert that S. Rajaratnam was one of the greatest leaders I met. Sadly, few in Singapore understand how great Rajaratnam was. This well-researched comprehensive volume by Irene Ng therefore fills a real need. Both Singaporeans and non-Singaporeans will benefit a lot from reading it." - Kishore Mahbubani, Dean, Lee Kuan Yew School of Public Policy, National University of Singapore "Rajaratnam is one of the founding fathers of modern Singapore. He was Singapore's first and longest serving foreign minister. He was a rebel and a revolutionary. He was an intellectual and a man of action. In this wonderful book, Irene Ng tells the story of this remarkable leader of Singapore. I found the book both enjoyable and insightful." - Tommy Koh, Ambassador-At-Large, Singapore